New approach to the analysis of the contact surfaces of rolling kinematic couple - Beneš, Libor; Kaloč, Rudolf; Minář, Luboš (Transport, 2010)
All physical processes of contact phenomenon especially a slip mechanism occur in the superficial layers related to changes in the micro/macro‐geometry of the surface. It is also the area where thermo‐mechanical processes of non‐isothermal nature arise. The persistent problems of damage to contact surfaces when being dynamically strained may only be gradually resolved using up‐to‐date metallographic methods, i.e. an experimental analysis of samples taken from the contact‐stressed areas. This paper deals with a new theoretical approach to the loading analysis of contact surfaces during rolling and gives basic information about the study on the influence of dynamical loading in the contact area with the possible occurrence of wave effects in contact with the adhesion drive of a rail vehicle (as an example). The experimental part is based on laboratory testing applying a new‐type designed device.First published online: 10 Feb 2011